EXPLORING PRE-SERVICE TEACHER BELIEFS ON THE USE OF DIGITAL STORYTELLING DURING TEACHING PRACTICUM CONTEXT - Muhammad Affan Ridho; David Imamyartha; Asih Santihastuti (Universitas PGRI Sumatera Barat, 2026)
Digital storytelling (DTS) has become a method that has received significant positive attention in English as a foreign language (EFL) classroom. Although numerous empirical studies have been widely documented, in-depth research on pre-service English teachers’ experiences implementing DTS in real classroom setting remains scarce. Many are familiar with DTS, but their beliefs about integrating Digital Storytelling into their teaching practice remain elusive. This research employed a case study design conducted at two different state universities in East Java, Indonesia. Semi-structured interviews were conducted with two pre-service English teachers during the same semester to collect data on their beliefs about implementing digital storytelling in their teaching practice. The data were analyzed using thematic analysis. This analysis yielded three key findings: (1) Pre-service teacher professional reflections and beliefs regarding the use of digital storytelling; (2) Pre-service teachers' pedagogical barriers and strategies in teaching DTS; and (3) The role of pre-service teachers in integrating local cultural values. This study shows that equipping pre-service teachers with in-depth pedagogical skills in digital storytelling will increase their technological pedagogical and content pedagogical knowledge (TPACK) capacity and encourage them to develo creative and innovative pedagogical skills in teaching English.